Umbilical Cord Blood and UC-MSCs Combined with Low-Dose Immunosuppressant in the Treatment of Elderly Patients with Pure Red Cell Aplastic: A Case Series - Zhu, Wei-Wei; Zhuang, Sujing; Yu, Zhe; Li, Xin; Han, Tian-Jie; Ma, Yue; Li, Li-Jun; Zhao, Zhi-Rui (Current Stem Cell Research & Therapy, 2025)
Introduction At present, cyclosporine (CsA) is the first-line treatment for Pure Red Cell Aplasia (PRCA), but CsA administration can be associated with a number of side effects due to its high toxicity. Therefore, it is urgent to explore a safe and effective treatment for elderly patients who cannot be treated with conventional doses of CsA, especially those with multiple complications. Allogeneic Stem Cell Transplantation (ASCT) for PRCA is a promising treatment, but reports of using umbilical cord blood (UCB) are very rare. Case Presentation In this report, UCB and umbilical cord mesenchymal stem cells (UC-MSCs) combined with low-dose CsA (1-3mg/kg/d) were used to treat 3 elderly patients who were diagnosed with PRCA combined with multiple complications in heart, lung, and renal. The treatments were successful without complications, and 12 months after stem cell infusion, the blood tests of the patients came normal. Moreover, the function of the liver, heart, and kidney continued to be stable. Conclusion This report provides an effective regimen of using UCB and UC-MSCs combined with low-dose CsA (1-3 mg/kg/d) to treat PRCA, especially for elderly patients with multiple complications who cannot use the conventional dosage.
Keywords: cyclosporine A